2015
DOI: 10.4236/jcc.2015.32002
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Control Structures for Reconfigurable Petri Nets

Abstract: Software systems are increasingly executed in dynamic infrastructures. These infrastructures are dynamic as they are themselves subject to change as they support various applications that may or may not share some of the resources. Dynamic software systems become more and more important, but are difficult to handle. Modeling and simulating dynamic systems requires the representation of their processes and the system changes within one model. To that effect, reconfigurable Petri nets consist of a Petri net and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Given their semantic richness and their theoretical foundation, RONs have benefited from a particular interest, both from the research community and from software firms. Nowadays, it is observed that various providers offer free and downloadable software tools such as RON-Editor (Biermann et al, 2007) and ReConnect (Ede et al, 2012) that are used to simulate and analyze RONs models. Further, such tools allow the representation of the system functionalities, where the dynamic at the micro-level and macro-level, the applied transformations' rules, and the system's configurations set are represented.…”
Section: = ( )mentioning
confidence: 99%
“…Given their semantic richness and their theoretical foundation, RONs have benefited from a particular interest, both from the research community and from software firms. Nowadays, it is observed that various providers offer free and downloadable software tools such as RON-Editor (Biermann et al, 2007) and ReConnect (Ede et al, 2012) that are used to simulate and analyze RONs models. Further, such tools allow the representation of the system functionalities, where the dynamic at the micro-level and macro-level, the applied transformations' rules, and the system's configurations set are represented.…”
Section: = ( )mentioning
confidence: 99%